Macrophage migration inhibitory factor promotes tumor aggressiveness of esophageal squamous cell carcinoma via activation of Akt and inactivation of GSK3β. (1st January 2018) - Liu, Rui-Min; Sun, Dan-Ni; Jiao, Ye-Lin; Wang, Pan; Zhang, Juan; Wang, Ming; Ma, Jin; Sun, Man; Gu, Bian-Li; Chen, Pan; Liu, Ke; Ma, Heng; et al.
Abstract: The pleiotropic pro-inflammatory cytokine, macrophage migration inhibitory factor (MIF), represents an important link between chronic inflammation and tumorigenesis. Although accumulating evidence demonstrates that MIF overexpression is implicated in the development and progression of multiple cancers, including esophageal squamous cell carcinoma (ESCC), the molecular mechanisms underlying its tumor-promoting roles in ESCC remain unclear. In the present study, we observed that MIF is overexpressed in ESCC and correlated significantly with lymph node metastasis, advanced clinical stage, and poor survival of ESCC. MIF knockdown attenuated the proliferation, migration, and invasion of ESCC cells in vitro and in vivo . Moreover, blockage of MIF expression decreased the activation of the Akt, MEK/ERK, and NF-κB pathways and enhanced sensitivity to apoptosis. Meanwhile, repression of MIF expression resulted in activation of glycogen synthase kinase 3 beta (GSK3β) and subsequent decrease of active β-catenin, as well as its downstream targets including cyclin D1, matrix metalloproteinase (MMP)-7, c-myc, and c-Jun. Collectively, our results provided mechanistic insights into the tumor-promoting role of MIF in ESCC, and suggested that MIF represents a potential therapeutic target for treatment of ESCC.